2018
DOI: 10.2106/jbjs.17.01341
|View full text |Cite
|
Sign up to set email alerts
|

The Demographic and Geographic Trends of Meniscal Procedures in New York State

Abstract: Background: The purpose of this study was to examine the geographic and demographic variations and time trends of different types of meniscal procedures in New York State to determine whether disparities exist in access to treatment. Methods: The New York Statewide Planning and Research Cooperative System (SPARCS) outpatient database was reviewed to identify patients who underwent elective, primary knee arthroscopy between January 1, 2003, and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Rural areas across the United States could potentially lag behind larger, metropolitan areas. 46 However, all regions across the United States demonstrated similarly consistent trends away from meniscectomy, with the exception of the Northwest (Figure 3). This observed difference is possibly attributable to the relatively lower case volume seen in the Northwest compared with other regions, thus making case trends more difficult to establish.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Rural areas across the United States could potentially lag behind larger, metropolitan areas. 46 However, all regions across the United States demonstrated similarly consistent trends away from meniscectomy, with the exception of the Northwest (Figure 3). This observed difference is possibly attributable to the relatively lower case volume seen in the Northwest compared with other regions, thus making case trends more difficult to establish.…”
Section: Discussionmentioning
confidence: 84%
“…This added understanding of meniscal function, advancement of repair techniques, recognition of meniscal root tears and meniscocapsular separation, and evidence that some tears have more ability to heal than initially believed, have led to more interest in meniscal preservation procedures. 19,23,31,38,46 The combination of these 2 shifts in approach to meniscal pathology should be seen in the practice patterns of recently trained orthopaedic surgeons. Parker et al, 39 in 2016, demonstrated an increase in meniscal repair among sports fellowship-trained surgeons.…”
mentioning
confidence: 99%
“… 33 Meniscal repairs have increased significantly over the past 10 years because repair techniques have improved and because meniscal repair better preserves the knee joint compared with meniscectomy in appropriately selected patients. 26 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…7,15,28,29,51 Knee arthroscopy and related procedures such as anterior cruciate ligament reconstruction (ACLR), meniscal repair, and partial meniscectomy have also continued to grow in volume. 22,23,25,32,36,40,50,60 Despite the growing use of knee, shoulder, and hip arthroscopy, there is a paucity of information regarding postoperative opioid prescribing patterns and use after arthroscopic procedures. This systematic review aims to examine and summarize the trends in prescribing practices and postoperative opioid consumption among patients undergoing sports medicine procedures.…”
mentioning
confidence: 99%